6th International Conference on Spoken Language Processing (ICSLP 2000) 2000
DOI: 10.21437/icslp.2000-373
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to the IST-HLT project speech-driven multimodal automatic directory assistance (SMADA)

Abstract: The following full text is an author's version which may differ from the publisher's version.For additional information about this publication click this link. http://hdl.handle.net/2066/75039Please be advised that this information was generated on 2022-08-08 and may be subject to change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In our experiment we have seen little positive effect of training a complete set of sub-word models on speech recorded in the application. In [3] it is shown that inclusion of a small number of application specific sub-word units does improve perform ance on a city name recognition task. Including an even smaller number of whole word models for the largest cities improves performance even further.…”
Section: Resultsmentioning
confidence: 99%
“…In our experiment we have seen little positive effect of training a complete set of sub-word models on speech recorded in the application. In [3] it is shown that inclusion of a small number of application specific sub-word units does improve perform ance on a city name recognition task. Including an even smaller number of whole word models for the largest cities improves performance even further.…”
Section: Resultsmentioning
confidence: 99%